Efeito da sinterização e da moagem de alta energia na microestrutura e nas propriedades mecânicas em ligas de alumínio recicladas a partir de latas de bebidas - Souza, José Raelson Pereira de (2017)
This work presents the study of the production and characterization of aluminum recycling from beverage cans composed of aluminum alloys AA3004, 5042 and 5182, using high energy grinding and powder metallurgy. The cans were selected, punched and ground to obtain the metallic powder under different milling times (1h, 1h30min and 2h). The obtained powder was compacted at a load of 400 MPa and sintered at 600 ° C for two hours. For characterization of the aluminum powder, XRD, SEM and EDS analyzes were performed, and laser grading; While the material consolidated by sintering, in addition to the analyzes via DRX, SEM and EDS, was also characterized by Vickers dilatometry, compression and microhardness tests. The size of the particles and their relationship to the properties of the aluminum alloy were evaluated. The processing route adopted resulted in the effective compaction of the aluminum powder from the beverage cans mill, but with porosity, typical of sintered metals. A high incidence of precipitates of the Al6Mn phase dispersed in the Al-alpha matrix (CFC) was observed. The samples presented variations in their mechanical properties as a function of milling time. The porosity and microstructure of the alloy may have influenced the mechanical properties resulting in the dissimilar behavior between the compressive strength and microhardness. The compressive strength increased from 105 N / mm² with 1h grinding to 120 N / mm² with 1h30min and decreasing to 110N / mm² with 2h grinding, but the ductility presented little variation. The hardness was 56.43 HV, 66.52 HV and 92.21 HV for the times of 1h, 1h30min and 2h, respectively.